Ultrafine Particle Recovery Using Thin Permeable Films - Borrow, Daniel J.; van Netten, Kim; Galvin, Kevin P. (Frontiers in Chemistry, 2018)
The selective recovery of ultrafine, <10 µm, particles remains a significant challenge in the minerals industry. Indeed, these particles often report to tailings impoundments, resulting in under-utilisation of mined resources and the need for tailings dams. Recently, a technique has been developed offering the potential to selectively recover particles down to <1 µm in size. This technique, originally inspired by oil agglomeration, uses a high internal-phase water in oil emulsion as a binder to selectively agglomerate hydrophobic particles. Due to the significant concentration of the dispersed aqueous phase, ~ 95%, the continuous organic phase forms a network of very thin, permeable films, estimated to be 60 nm thick. These are stabilised by an emulsifier. In the high shear field of the agglomeration process, the binder is fragmented into smaller hydrophobic portions, delivering its thin film coating to the adhering hydrophobic particles. Permeation of water across the thin films eliminates the viscous hydrodynamic resistance, permitting sub-micron particle recovery to occur at rates similar to those for particles considerably larger in size. This recovery occurs within seconds under intense mixing. In this study, a model system consisting of magnetite, with a Sauter mean diameter of 11.4 µm, was agglomerated using the water in oil emulsion binder. The binder, which contained the emulsifier sorbitan monooleate, appeared to also act as a collector for the magnetite, thus no separate particle conditioning step was required. Curiously, however, the binder requirements were higher than expected. Further investigations concerning the stability of the binder revealed that the magnetite particles were causing rapid binder degradation. Therefore, prior to agglomeration using the binder, the particles were conditioned with sorbitan monooleate to render them hydrophobic. This pre-conditioning led to significant reductions in the binder dosage required to achieve agglomeration. Moreover, the resulting dosage matched that predicted by a model silica system for the same specific hydrophobic surface area, thus allowing a model to be validated based on the required binder dosage for a known hydrophobic surface area. Examination of binder stability in the presence of conditioned magnetite revealed that the now hydrophobic particles stabilised the binder.